Transient Pulse Test for Non-Darcy Flow Behaviors and Hydromechanical Coupling Effect of Fractured Limestone - JianChao Cheng; YanLin Zhao; Yang Li; Tao Tan; Le Chang (Advances in Civil Engineering)
In this paper, the transient pulse test is used to study the permeability and hydromechanical coupling effect of the fractured limestone. The permeability parameters (permeability, β factor of non-Darcy flow, and acceleration coefficient) of non-Darcy flow in fractured limestone are obtained by experimental data. The experimental results show that, in the process of transient seepage test of fractured Maokou limestone, the relationship between hydraulic pressure gradient and seepage velocity does not conform to Darcy’s law but meets Forchimer relationship. The relationship between hydraulic pressure difference and time can be fitted by quartic polynomial. The larger the confining pressure is, the more obvious the non-Darcy seepage effect of fractured rock seepage is. The seepage of rock fracture under high confining pressure is a highly nonlinear time-varying seepage. The permeability coefficient of rock decreases with the increase of volume stress. Under the action of low volume stress, the relationship between permeability coefficient and stress is more sensitive, while under the action of high volume stress, the relationship between permeability coefficient and volume stress is not significant. In the process of volume stress increasing, the β factor of non-Darcy flow appears negative. Under the action of low volume stress, the acceleration coefficient and β factor of non-Darcy flow increase, while under the action of high volume stress, the acceleration coefficient and β factor of non-Darcy flow decrease.